Microglia, rather than bacterial factors, mediate bovine neutrophil chemotaxis in neurolisteriosis - S. Bagatella; N. Haghayegh Jahromi; C. Monney; M. Polidori; F.M. Gall; F. Serra; R. Riedl; B. Engelhardt; A. Oevermann (Journal of Comparative Pathology, 2023)

Toxic effects of lead in plants grown in brazilian soils - Geraldo S. Cândido; Gabriel C. Martins; Isabela C. F. Vasques; Francielle R. D. Lima; Polyana Pereira; Mateus M. Engelhardt; Rayner H. C. L. Reis; João José Marques (Ecotoxicology, 2020)

Evaluation of mercury phytoavailability in Oxisols - Francielle R. D. Lima; Mateus M. Engelhardt; Isabela C. F. Vasques; Gabriel C. Martins; Geraldo S. Cândido; Polyana Pereira; Rayner H. C. L. Reis; Aline O. Silva; Luiz Roberto G. Guilherme; João José Marques (Environmental Science and Pollution Research, 2019)

Timing of risk reducing mastectomy in breast cancer patients carrying a BRCA1/2 mutation: retrospective data from the Dutch HEBON study - M. R. Wevers; M. K. Schmidt; E. G. Engelhardt; S. Verhoef; M. J. Hooning; M. Kriege; C. Seynaeve; M. Collée; C. J. van Asperen; R. A. E. M. Tollenaar; L. B. Koppert; A. J. Witkamp; et al. (Familial Cancer, 2015)

VLBI-derived troposphere parameters during CONT08 - R. Heinkelmann; J. Böhm; S. Bolotin; G. Engelhardt; R. Haas; R. Lanotte; D. S. MacMillan; M. Negusini; E. Skurikhina; O. Titov; H. Schuh (Journal of Geodesy, 2011)

The role of landscape connectivity in assembling exotic plant communities: a network analysis - Emily S. Minor; Samantha M. Tessel; Katharina A. M. Engelhardt; Todd R. Lookingbill (Ecology, 2009)
Landscape fragmentation and exotic species invasions are two modern‐day forces that have strong and largely irreversible effects on native diversity worldwide. The spatial arrangement of habitat fragments is critical in affecting movement of individuals through a landscape, but little is known about how invasive species respond to landscape configuration relative to native species. This information is crucial for managing the global threat of invasive species spread. Using network analysis and partial Mantel tests to control for covarying environmental conditions, we show that forest plant communities in a fragmented landscape have spatial structure that is best captured by a network representation of landscape connectivity. This spatial structure is less pronounced in invasive species and exotic species dispersed by animals. Our research suggests that invasive species can spread more easily in fragmented landscapes than native species, which may make communities more homogeneous over time.

Defective jejunal and colonic salt absorption and alteredNa+/H+ exchanger 3 (NHE3) activity in NHE regulatory factor 1 (NHERF1) adaptor protein-deficient mice - N. Broere; M. Chen; A. Cinar; A. K. Singh; J. Hillesheim; B. Riederer; M. Lünnemann; I. Rottinghaus; A. Krabbenhöft; R. Engelhardt; B. Rausch; E. J. Weinman; et al. (Pflügers Archiv - European Journal of Physiology, 2009)

Combination of long time-series of troposphere zenith delays observed by VLBI - R. Heinkelmann; J. Boehm; H. Schuh; S. Bolotin; G. Engelhardt; D. S. MacMillan; M. Negusini; E. Skurikhina; V. Tesmer; O. Titov (Journal of Geodesy, 2007)

The evolution of female copulation calls in primates: a review and a new model - Gauri R. Pradhan; Antje Engelhardt; Carel P. van Schaik; Dario Maestripieri (Behavioral Ecology and Sociobiology, 2006)

Accidental intrathecal infusion of cefotiam: clinical presentation and management - G. Brssner; K. Engelhardt; R. Beer; B. Pfausler; A. Georgopoulos; E. Schmutzhard (European Journal of Clinical Pharmacology, 2004)

Fish recruitment in a canal with intensive navigation: implications for ecosystem management - R. Arlinghaus; C. Engelhardt; A. Sukhodolov; C. Wolter (Journal of Fish Biology, 2002)
The young‐of‐the‐year (YOY) fish community in Oder‐Havel‐Kanal, a navigable canal in the German lowlands, assessed from May to October 1999, was dominated by tolerant species especially roach Rutilus rutilus and perch Perca fluviatilis . Roach dominance was high in May and June and low during the rest of the sampling period. The dominance pattern of perch was inversely related to that of roach. Significantly higher densities of significantly smaller YOY fishes were found in bays compared with the straight reaches of the main channel which was the result of an aggregation of 0+ year roach in bays in May and June. Parallel to low structural variability (spawning and nursery habitats), the intensive ship traffic may have been a major force structuring the fish communities in the canals. Measured ship‐induced flow velocity in straight reaches was about four times higher than in bays of the canal. Maximum flow velocities caused by barge tows were also four times higher than those induced by pleasure boats. The study demonstrated the relatively low fish reproductive potential of a navigable, artificially embanked lowland canal. To improve fish reproduction, modification of canal banks is highly advisable to preserve existing bays and tributaries and even to create additional ones.

ITRF coordinates and plate velocities from repeated GPS campaigns in Antarctica - an analysis based on different individual solutions - R. Dietrich; R. Dach; G. Engelhardt; J. Ihde; W. Korth; H.-J. Kutterer; K. Lindner; M. Mayer; F. Menge; H. Miller; C. Müller; W. Niemeier; et al. (Journal of Geodesy, 2001)

Surface pH at the Basolateral Membrane of the Caecal Mucosa of Guinea Pig - S. Kirschberger; R. Busche; W. von Engelhardt (The Journal of Membrane Biology, 1999)

Induction of mixed function oxidases by petroleum in the American eel,Anguilla rostrata - M. E. Nava; F. R. Engelhardt (Archives of Environmental Contamination and Toxicology, 1982)

Metabolism of o-phthalic acid by different gram-negative and gram-positive soil bacteria - Gabriele Engelhardt; P. R. Wallnfer; H. G. Rast; F. Fiedler (Archives of Microbiology, 1976)